Dicamba-Tolerant Soybean Response to 2,4-D Micro-Rates at Three Growth Stages: Dicamba-Tolerant Soybean Response to 2,4-D Micro-Rates at Three Growth Stages - knezevic, Stevan (European Journal of Applied Sciences, 2021)
While dicamba and 2,4-D belong to the same herbicide group, dicamba- and 2,4-D-tolerant soybeans are not cross-resistant. A study was conducted to investigate dicamba-tolerant (DT) soybean response to 2,4-D micro-rates at three growth stages. The study used a randomized complete block design with six replications and a split-plot treatment arrangement. Main plots consisted of three 2,4-D application times [second trifoliate (V2); beginning of flowering (R1); and full flowering (R2)] and subplots consisted of six 2,4-D micro-rates (1/5; 1/10; 1/50; 1/100; 1/500; and 1/1,000 of the label recommended dose of 1,120 g ae ha-1) and a check with no herbicide applied. DT soybean injury symptoms were assessed at 7, 14 and 21 days after treatment (DAT). Yield components, grain yield and yield loss were estimated. The greatest soybean injury (59%) at 21 DAT, delay in canopy closure (16.8 d), and reduction in number of branches plant-1 (52%), pods plant-1 (38%) and 100 seed weight (16%) which ultimately resulted in yield loss (78%) was caused by 1/5 of the label recommended dose of 2,4-D (214 g ae ha-1) at R1 growth stage. Based on effective dose (ED) estimates, 8.66 g ae ha-1 2,4-D caused 0.22 Mg ha-1 (5%) yield loss in DT soybean at R1 but a 1.34- and 2.11-fold higher dose of the same herbicide was required to cause equal yield loss at R2 and V2 growth stages, respectively. Similarly, the number of branches plant-1, pods plant-1 and flowers plant-1 were more sensitive to 2,4-D at R1 than V2 and R2 growth stages with the latter being the most sensitive yield component. On the other hand, 100 seed weight was 3.1- and 4.5-fold more sensitive to 2,4-D at R2 than R1 and V2 growth stages, respectively. Overall, these results showed that DT soybean is most sensitivity to 2,4-D at R1.